Depression and Multiple Rehospitalizations in Patients With Heart Failure - Freedland, Kenneth E. (Clin Cardiol, 2016)
BACKGROUND: There have been few studies of the effect of depression on rehospitalization in patients with heart failure (HF), and even fewer on its role in multiple rehospitalizations. HYPOTHESIS: Depression is an independent risk factor for multiple readmissions in patients with HF. METHODS: A cohort of 662 patients with HF who were discharged alive after hospitalization were interviewed to evaluate symptoms of depression and were followed for 1 year. All‐cause readmissions were documented by chart review. A marginal proportional rates model was used to model the effect of depression on the rate of rehospitalization with adjustment for known predictors of HF outcomes. RESULTS: Depression symptoms predicted multiple readmissions (adjusted hazard ratio [HR]: 1.08, 95% confidence interval [CI]: 1.03‐1.13, P = 0.0008). Compared with patients without depression, those who met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) criteria for major depression at index were at the highest risk for multiple rehospitalizations (HR: 1.51, 95% CI: 1.15‐1.97, P = 0.003). CONCLUSIONS: Depression is an independent risk factor for multiple all‐cause readmissions in patients with HF.